Relationship of Motility Activation to Lipid Composition, Protein Profile, and Swelling Rate of Burbot Lota lota Spermatozoon Following Change of Temperature and Osmolality - Dadras, Hadiseh; Policar, Tomas; Loginov, Dmitry; Boryshpolets, Sergii; Loginova, Yana; Sampels, Sabine; Sotnikov, Anatolii; Kholodnyy, Vitaliy; Sterba, Jan; Xin, Miaomiao; Dzyuba, Borys (Frontiers in Marine Science, 2021)
Despite available information on the roles of osmotic pressure, potassium (K+), and calcium (Ca2+) in activation of Eurasian burbot spermatozoon motility, the changes in milt biochemical composition and mechanisms underlying their activation at temperatures above optimal spawning temperature is still unclear. We explored spermatozoon swelling, lipid composition and proteome in relation to osmolality and temperature of swimming medium. The result revealed that temperature increment from 4 to 30 ℃ increases burbot spermatozoa vulnerability to osmotic pressure, decreasing motility in extremely hypotonic media, and the presence of Ca2+ decreases swelling of spermatozoa. No spermatozoon swelling was observed in non-ionic isotonic media at all studied temperatures. A role of swelling in activation of spermatozoa motility at 30 ℃ was rejected. No differences were found in protein profile and lipid composition with respect to activation of burbot spermatozoa at 30 ℃. Burbot spermatozoon activation occurs at 30 ℃ without modification of the spermatozoon membrane. Elucidation of the intrinsic signaling pathway of burbot spermatozoon spontaneous activation requires further study.